2015
DOI: 10.1016/j.vaccine.2015.01.026
|View full text |Cite
|
Sign up to set email alerts
|

An H10N8 influenza virus vaccine strain and mouse challenge model based on the human isolate A/Jiangxi-Donghu/346/13

Abstract: Three human cases of H10N8 viruses were reported in China in late 2013 and early 2014, two of which were fatal. This was the first time the H10N8 subtype has been detected in humans and no vaccine candidates or antibody therapy has been developed for these viruses so far. We developed an H10N8 vaccine candidate virus based on A/Jiangxi-Donghu/346/13 that can also be used in a murine challenge model for vaccine and monoclonal antibody research. The vaccine virus is a 6:2 re-assortant virus expressing the surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Protection against heterologous H10 challenge was demonstrated using vaccination with either mono- or quadri-subtype VLPs. Other strategies to protect from H10 influenza include HA stalk- and NA-specific monoclonal antibodies, as well as a 6:2 reassortant virus expressing the surface glycoproteins of A/Jiangxi-Donghu/346/13 (H10N8) on an A/Puerto Rico/8/34 backbone [44, 45]. Although in the current study we did not challenge vaccinated animals with multiple influenza viruses, we previously showed that VLPs displaying three HA subtypes are capable of protecting against multiple homologous virus challenges [20, 21, 42].…”
Section: Discussionmentioning
confidence: 99%
“…Protection against heterologous H10 challenge was demonstrated using vaccination with either mono- or quadri-subtype VLPs. Other strategies to protect from H10 influenza include HA stalk- and NA-specific monoclonal antibodies, as well as a 6:2 reassortant virus expressing the surface glycoproteins of A/Jiangxi-Donghu/346/13 (H10N8) on an A/Puerto Rico/8/34 backbone [44, 45]. Although in the current study we did not challenge vaccinated animals with multiple influenza viruses, we previously showed that VLPs displaying three HA subtypes are capable of protecting against multiple homologous virus challenges [20, 21, 42].…”
Section: Discussionmentioning
confidence: 99%
“…At 2 h after treatment, the mice were anesthetized using a ketamine-xylazine mixture and infected with 5Ï« the 50% lethal dose (LD 50 ) of JD13 (H10N8) virus diluted in PBS (pH 7.4). The LD 50 of this virus in BALB/c mice has been previously determined and characterized in detail (21). In a therapeutic setting, mice received a 5-mg/kg dose of each antibody intraperitoneally 48 h after infection.…”
Section: Fig 1 Anti-h10 and Anti-n8 Antibodies Display Heterologous Cmentioning
confidence: 99%
“…The influenza viruses A/mallard/IA/10BM01929/10 (H10N7), A/Northern shoveler/Alaska/7MP1708/07 (H3N8), and JD13 (A/Puerto Rico/8/1934 [PR8, H1N1] internal genes and hemagglutinin [HA] and neuraminidase [NA] from A/Jiangxi-Donghu/346/13 [H10N8]) (21) were grown in 8-to 10-day-old embryonated chicken eggs, and titers were determined on MDCK cells in the presence of TPCK (tolylsulfonyl phenylalanyl chloromethyl ketone)-treated trypsin. The latter JD13 reassortant virus was rescued and characterized as previously described (21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…an H3N2 variant that spilled over into humans attending agricultural shows in the early 2010s, H3N2v (Jhung et al, 2013). In addition, zoonotic infections with other viruses from poultry or wild birds have occurred, including for example H7N7 (Fouchier et al, 2004), H10N8 (Wohlbold et al, 2015), H6N1 (Wei et al, 2013), H9N2 (Butt et al, 2005), and H5N6 (Yang et al, 2015); for more examples and a fuller discussion see (Short et al, 2015). The severity of zoonotic influenza A infections ranges from clinically inapparent (Gomaa et al, 2015; To et al, 2016) to fatal (de Jong et al, 2006; Gao et al, 2013).…”
Section: Introductionmentioning
confidence: 99%